Finding privacy in the red-light district: an analysis of Victorian era medicine bottles from the Vanoli Site (5OR.30) in Ouray, Colorado - Horobik, Heather A., author; Van Buren, Mary, advisor; Magennis, Ann, committee member; Robinson, Narda, committee member (Colorado State University. Libraries, 2011)
A sample of bottles from the Vanoli Site (5OR.30), part of a Victorian era red-light district in Ouray, Colorado are examined. Previous archaeological studies involving the pattern analysis of brothel and red-light district assemblages have revealed high frequencies of medicine bottles. The purpose of this project was to determine whether a sense of privacy regarding health existed and how it could influence disposal patterns. The quantity and type of medicine bottles excavated from two pairs of middens and privies were compared. A concept of privacy was discovered to have significantly affected the location and frequency of medicine bottle disposal. A greater percentage of medicine bottles was deposited in privies, the private locations, rather than the more visually open and accessible middens. This study concludes that, while higher percentages of medicine bottles are found within brothel and red-light district locations, other factors such as privacy and feature type may affect the artifact patterns associated with such sites.
Keywords: archaeology; brothel; health; medicine; prostitution; Victorian